Evolution of the Instructional Design in a Series of Online Workshops | L’évolution d’un design pédagogique dans le développement d’ateliers en ligne - Patry, Anne; Campbell Brown, Elizabeth; Rousseau, Rémi; Caron, Jeanette (Canadian Journal of Learning and Technology, 2015)
This case recounts the story of the design and production of a series of online workshops for French-speaking healthcare professionals in Canada. The project spans a couple of years and, despite encountering some challenges, succeeds in large part because of its strong foundation: the instructional design. This case study features an instructional designer from a central Canadian university and three SMEs. The main design issues highlighted are the target population’s limited availability for continuing education, the SME’s lack of knowledge of the instructional design process, the magnitude of this project with its national scope but limited time frame and human resources, as well as personnel changes among the SMEs and the instructional design team. This case outlines how the project team deals with these challenges to produce a series of online workshops that provide high quality training in French to healthcare professionals across Canada.